Letter (copy) : Bombing of towns in Spain - Citrine, Walter, 1887-1983
012b-0005-001 WMC/WJB/MS/227 International 31st January, 1938. The Rt. Hon. Neville Chamberlain, M.P., Prime Minister, 10, Downing Street, Whitehall S.W.1. Dear Mr. Chamberlain, Bombing of Towns in Spain. I feel impelled to express to you the deep anxiety and horror which is felt in the Labour Movement, at the terrible massacre of men, women and children in the cities of Spain. Especially are we appalled at this last bombing raid on Barcelona, which has brought death and injury to hundreds of people. This is all the more tragic on account of the recent offer of the Government's Minister of Defence, Señor Prieto, to agree to the arrangement of an aerial truce so far as open towns are concerned. I know that you and your colleagues are not unmoved at these ruthless acts of barbarity, and we do not forget that you and other Governments attempted at the beginning of the conflict to humanise the war - indeed, had the project contemplated obtained acceptance, these crimes against humanity would not have taken place. I venture sincerely to appeal to you again to initiate some such step, so as to induce the leaders of both sides in Spain to agree to refrain from the bombing of open cities. It is imperative that some such arrangement should be come to at an early date, if the lives of thousands of innocent people are to be saved and if the cities of Spain are to be preserved from [...] and wanton destruction. In the name of our common civilisation, [...] again urge you to make the effort to achiev[...] Yours faithfully General Secretary 292/946/12b/5